2017
DOI: 10.1155/2017/9743280
|View full text |Cite
|
Sign up to set email alerts
|

NLRP3 Inflammasome Activation‐Mediated Pyroptosis Aggravates Myocardial Ischemia/Reperfusion Injury in Diabetic Rats

Abstract: The reactive oxygen species- (ROS-) induced nod-like receptor protein-3 (NLRP3) inflammasome triggers sterile inflammatory responses and pyroptosis, which is a proinflammatory form of programmed cell death initiated by the activation of inflammatory caspases. NLRP3 inflammasome activation plays an important role in myocardial ischemia/reperfusion (MI/R) injury. Our present study investigated whether diabetes aggravated MI/R injury through NLRP3 inflammasome-mediated pyroptosis. Type 1 diabetic rat model was es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
225
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 305 publications
(238 citation statements)
references
References 60 publications
13
225
0
Order By: Relevance
“…These findings suggest that CASP1 may be a better explanatory marker for an adverse prognosis of DN. Activation of NLRP3 and caspase 1 may have led to maturation of inflammatory cytokines and induction of pyroptosis in an animal model . Pyroptosis in DK has been suggested to indicate an adverse prognosis of DN, at least in animal models, and the present observation replicates the phenomenon in humans.…”
Section: Commentssupporting
confidence: 75%
See 2 more Smart Citations
“…These findings suggest that CASP1 may be a better explanatory marker for an adverse prognosis of DN. Activation of NLRP3 and caspase 1 may have led to maturation of inflammatory cytokines and induction of pyroptosis in an animal model . Pyroptosis in DK has been suggested to indicate an adverse prognosis of DN, at least in animal models, and the present observation replicates the phenomenon in humans.…”
Section: Commentssupporting
confidence: 75%
“…It has been documented that treatment of naïve DM subjects is associated with elevated levels of the nod like receptor (NLR)‐dependent inflammasome complex (IC) . In a rat model, IC downregulation after administration of antidiabetic medication has been documented in vitro . The role of the NLR‐dependent‐IC (NLR family pyrin domain containing 3 (NLRP3), Caspase 1 (CASP1) and PYD and CARD domain containing (PYCARD)) in the pathogenesis of DN has been recently documented in animals, and in humans but studies are limited.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…B, Representative bands of western blot analysis for the expression of EZH2 and bar graph showed the quantification, n = 3; Two-tailed t test was used for the statistical analysis; Values are expressed as the mean ± SEM. 23,25,31,32 At the cellular level, our further study revealed that the ablation of ROS with NAC abolished H/Rmediated elevation of pyroptosis-related protein expression and caspase-1 activity, and the induction in pyroptotic cells and LDH release strongly confirmed that pyroptosis was inhibited by decreased ROS generation. C-J, HK-2 cells were transfected with an siRNA against EZH2 or a negative control siRNA (si-NC) for 48 h and were pretreated with or without DZNeP at dose of 2.5 μM for 1 h before being exposed to H/R.…”
Section: Discussionsupporting
confidence: 58%
“…25 Briefly, cells were mixed with 1x assay buffer and were then stained with 2 μM calcein-AM and 4.5 μM PI at 37°C for 30 min. 25 Briefly, cells were mixed with 1x assay buffer and were then stained with 2 μM calcein-AM and 4.5 μM PI at 37°C for 30 min.…”
Section: Staining Assaymentioning
confidence: 99%